Retrorectal tumors: A case series - B. Bülent MENTEŞ; Osman KURUKAHVECİOĞLU and Bahadır EGE and Ahmet KARAMERCAN and Sezai LEVENTOĞLU and Ömer YAZICIOĞLU and Mehmet OĞUZ (Turkish Journal of Gastroenterology, 2019)
-